Novel insights into cardiac regeneration based on differential fetal and adult ovine heart transcriptomic analysis - Locatelli, Paola (2020)
The adult mammalian cardiomyocyte has a very limited capacity to reenter the cell cycle and advance into mitosis. Therefore, diseases characterized by lost contractile tissue usually evolve into myocardial remodeling and heart failure. Analyzing the cardiac transcriptome at different developmental stages in a large mammal closer to the human than laboratory rodents may serve to disclose positive and negative cardiomyocyte cell cycle regulators potentially targetable to induce cardiac regeneration in the clinical setting. Thus we aimed at characterizing the transcriptomic profiles of the early fetal, late fetal, and adult sheep heart by employing RNA-seq technique and bioinformatic analysis to detect protein-encoding genes that in some of the stages were turned off, turned on, or differentially expressed. Genes earlier proposed as positive cell cycle regulators such as cyclin A, cdk2, meis2, meis3, and PCNA showed higher expression in fetal hearts and lower in AH, as expected. In contrast, genes previously proposed as cell cycle inhibitors, such as meis1, p16, and sav1, tended to be higher in fetal than in adult hearts, suggesting that these genes are involved in cell processes other than cell cycle regulation. Additionally, we described Gene Ontology (GO) enrichment of different sets of genes. GO analysis revealed that differentially expressed gene sets were mainly associated with metabolic and cellular processes. The cell cycle-related genes fam64a, cdc20, and cdk1, and the metabolism-related genes pitx and adipoq showed strong differential expression between fetal and adult hearts, thus being potent candidates to be targeted in human cardiac regeneration strategies. NEW & NOTEWORTHY We characterized the transcriptomic profiles of the fetal and adult sheep hearts employing RNAseq technique and bioinformatic analyses to provide sets of transcripts whose variation in expression level may link them to a specific role in cell cycle regulation. It is important to remark that this study was performed in a large mammal closer to humans than laboratory rodents. In consequence, the results can be used for further translational studies in cardiac regeneration.